2019
DOI: 10.1111/jcmm.14136
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CXCL1 chemokine and CSF3 cytokine levels in myometrial cells by the MAFF transcription factor

Abstract: Cytokines play key roles in a variety of reproductive processes including normal parturition as well as preterm birth. Our previous data have shown that MAFF , a member of the MAF family of bZIP transcription factors, is rapidly induced by pro‐inflammatory cytokines in PHM 1‐31 myometrial cells. We performed loss‐of‐function studies in PHM 1‐31 cells to identify MAFF depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…But the downstream signal moleculars of this pathway in HCC are still unclear. Previous researches indicated that MafF participated in oxidant stress response, inflammatory response, and cell motility by regulating the transcription of related genes such as heme oxygenase 1 (HO-1) and matrix metalloproteinases (MMPs) 9,35 . More studies need to be performed to elucidate the exact downstream moleculars of the circ-ITCH/miR-224-5p/MafF pathway in HCC, which will provide a new perspective for early diagnostic biomarkers and potential therapeutic targets of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…But the downstream signal moleculars of this pathway in HCC are still unclear. Previous researches indicated that MafF participated in oxidant stress response, inflammatory response, and cell motility by regulating the transcription of related genes such as heme oxygenase 1 (HO-1) and matrix metalloproteinases (MMPs) 9,35 . More studies need to be performed to elucidate the exact downstream moleculars of the circ-ITCH/miR-224-5p/MafF pathway in HCC, which will provide a new perspective for early diagnostic biomarkers and potential therapeutic targets of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, WT1 has also been involved in cardiac development and disease(53-55), a link that was further supported by our phenome-wide association look-up results, since this region was associated with hypertension and cardiovascular disease (Supplementary Figure 3 and 4, Supplementary Tables 5 and 6). In this line, many associations we report point towards a link between metabolic and cardiovascular health and pelvic organ prolapse (KLF13, DUSP16, MAFF, VCL and LDAH), which was mirrored by positive genetic correlations with a range of cardiometabolic phenotypes (56)(57)(58)(59)(60)(61)(62)(63)(64)(65).…”
Section: Interpretation Of Findings and Comparison To Other Studiesmentioning
confidence: 91%
“…In Pde6b rd10 mice, Maff was highly upregulated. The MAFF protein can regulate photoreceptor gene expression and is closely associated with inflammatory responses in neuronal diseases (Katsuoka et al, 2003;Chevillard et al, 2007;Saliba et al, 2019). We speculate that constant MAFF activation may contribute to inflammatory processes in the microenvironment through pro-inflammatory cytokines or chemokines, thereby mediating photoreceptor cell death.…”
Section: Roles Of Transcription Factors In Regulating Rdmentioning
confidence: 92%